An innovative re-centering SMA-lead damper and its application to steel frame structures. (8th June 2018) - Li, Hong-Nan; Liu, Ming-Ming; Fu, Xing
Abstract: In this paper, an innovative re-centering damper is presented to reduce the residual deflection of civil structures under strong earthquakes. The schematic diagram of the proposed re-centering SMA-lead damper (RSLD) is provided first. Then the mechanical behaviors of all the sub-components are measured by the testing machine, followed by the proposal of mechanical model of the RSLD. Based on the experimental results, the mechanical model factors for each sub-component are determined by the data fitting method, which is then used to simulate the hysteresis loops of the damper. Meanwhile the experiment of the fabricated RSLD is carried out to study the influence of the loading rate and displacement amplitude on the mechanical properties. Finally, the response analysis of a six-story steel frame structure installed with different damper position configurations is performed, and the results reveal that the proposed RSLD has an outstanding re-centering capacity.